Discrimination, Social Exclusion and Vulnerability of the Garífuna Women in Guatemala; An Exploratory Study on Underlying Causes - Mulongoy, Melissa (Université d'Ottawa / University of Ottawa, 2013)
The Garífuna are the smallest ethnic minority group in Guatemala, living primarily in the city of Livingston (known as Labuga, Wadimalu in Garífuna) located along the Caribbean coastline. Their unique history, ethnicity and culture has allowed them to preserve their way of life for centuries on the one hand but has also separated them from mainstream Guatemalan society on the other hand. The afro-descendent Garífuna community forms a small part of the overall indigenous group in Guatemala alongside the Maya and the Xinca groups; however unlike the larger indigenous groups and the remaining non-indigenous population, the Garífuna are ignored and are not included in the groups in need of development assistance for education, health, employment and security. The exclusion is even more pronounced for Garífuna women. This study was conducted to understand the reasons for the discrimination, socio-economic exclusion and vulnerability of Garífuna women within the Guatemalan society, what is currently being done to address the challenges and barriers Garífuna women are facing, and what further changes need to take place to bring about a transformation in their situation.
Keywords: Garífuna; Garinagu; women; gender; Central America; Guatemala; human development; development; Sustainable development; afro descendent; ethnicity; Exclusion; race; Marginalisation